ULK1 phosphorylates Exo70 to suppress breast cancer metastasis - Liyuan Mao (Nature Portfolio, 2020)
Elevated expression of ULK1 is known to be inversely correlated with breast cancer metastasis. Here, the authors report Exo70 as a substrate of ULK1 that suppresses cancer metastasis, and show that ERK1/2 mediated phosphorylation of Exo70 leads to opposing effects on tumour cell invasion.